Boundary Spanning and Engineering: A Qualitative Systematic Review. Issue 3 (15th August 2018) - Jesiek, Brent K.; Mazzurco, Andrea; Buswell, Natascha T.; Thompson, Julia D.
Abstract: Background: Engineers are often expected to span organizational, cultural, stakeholder, geographic, temporal, and other boundaries. Yet, few studies on boundary spanning have appeared in the engineering education literature, suggesting the need for improved theoretical and conceptual foundations to guide empirical studies of boundary spanning in engineering. Purpose: To develop a more comprehensive understanding of boundary spanning, this study addresses five research questions: (a) What types of boundaries have been identified as topics of interest? (b) How are boundary spanners and boundary spanning defined? (c) What types of activities and behaviors comprise or have been linked to boundary spanning? (d) What individual competencies and characteristics have been proposed or studied as important for boundary spanning? and (e) What boundary spanning themes are most prominent in studies of engineers and other technical professionals? Scope/Method: Using a qualitative systematic review process, we identified and analyzed 72 scholarly papers from multiple disciplines. Multiple reviewers coded each paper using a hybrid deductive‐inductive content analysis process to identify key themes related to boundary spanning. Conclusions: The analysis resulted in a framework consisting of six boundary types, three types of roles and definitions, and five types of activities. Discussion of boundary spanning competencies was limited in the collected works, and only seven papers exclusively focused on engineers. We conclude by proposing boundary spanning as an important meta‐attribute for engineers and a promising lens for investigating engineering practice. We also relate our findings to the engineering education literature and suggest directions for future research.